Transforming Growth Factor-β: An Agent of Change in the Tumor Microenvironment - Stuelten, Christina H.; Zhang, Ying E. (Frontiers in Cell and Developmental Biology, 2021)
Transforming Growth Factor-β (TGF-β) is a key regulator of embryonic development, adult tissue homeostasis, and lesion repair. In tumors, TGF-β is a potent inhibitor of early stage tumorigenesis and promotes late stage tumor progression and metastasis. Here, we review the roles of TGF-β as well as components of its signaling pathways in tumorigenesis. We will discuss how a core property of TGF-β, namely its ability to change cell differentiation, leads to the transition of epithelial cells, endothelial cells and fibroblasts to a myofibroblastoid phenotype, changes differentiation and polarization of immune cells, and induces metabolic reprogramming of cells, all of which contribute to the progression of epithelial tumors.